Development of high school students' geometric thinking with particular emphasis on mathematically talented students - Győry, Ákos; Kónya, Eszter (Teaching Mathematics and Computer Science, 2018)
We carried out research using Zalman Usiskin's test (1982) and also a modified version of his test to see how the geometric approach of secondary school students (Grades 8-10) specialized in mathematics had changed. We observed two groups of students for several years. Our aim was to find a relation between the change of the mean of the van Hiele level of the students and the structure of the geometry syllabus. We also observed if there was a change in the geometric approach of the students during the summer holidays and if so, in what way it changed.